2022
DOI: 10.1088/1361-6463/ac99e8
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of release cloud from laser shock-loaded graphite and hydrocarbon targets: in search of diamonds

Abstract: This work presents first insights into the dynamics of free-surface release clouds from dynamically compressed polystyrene and pyrolytic graphite at pressures up to 200 GPa, where they transform into diamond or lonsdaleite, respectively. These ejecta clouds are released into either vacuum or various types of catcher systems, and are monitored with high-speed recordings (frame rates up to 10 MHz). Molecular dynamics simulations are used to give insights to the rate of diamond preservation throughout the free ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 81 publications
0
5
0
Order By: Relevance
“…We found that the results of our simulations do not match the experimental observations quantitatively but predict the disappearance of diamonds at conditions where they are still visible in the XRD. Despite these quantitative disparities, we argue that the qualitative trends can still be used to find promising approaches, guiding future recovery experiments 16 . The results of the simulations can help guide the design of future experiments, and the absolute values like disintegration and recrystallisation rates should always be benchmarked against experiments.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…We found that the results of our simulations do not match the experimental observations quantitatively but predict the disappearance of diamonds at conditions where they are still visible in the XRD. Despite these quantitative disparities, we argue that the qualitative trends can still be used to find promising approaches, guiding future recovery experiments 16 . The results of the simulations can help guide the design of future experiments, and the absolute values like disintegration and recrystallisation rates should always be benchmarked against experiments.…”
Section: Discussionmentioning
confidence: 97%
“…The low-temperature end of the so-called warm dense matter regime is poorly understood and thus, modelling structural transitions and chemistry is extraordinarily difficult and experimental benchmarks are vital 12 , 13 . Recent dynamic compression experiments of plastic materials combined with in situ X-ray scattering have found a surprisingly fast phase separation of carbon and hydrogen and the formation of nanodiamonds (NDs) on a sub-nanosecond timescale 4 , 14 16 . In previous experiments, nucleation rates of NDs in laser-driven shocks were higher than 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Post-mortem analysis of recovered samples would allow to use the wide range of materials characterization techniques (e.g. Raman spectroscopy, X-ray diffraction, electron microscopy, Auger electron spectroscopy) in order to find, identify and quantify the new materials generated 55 . This will enable a better understanding of the formation processes, possibly finding so far unknown novel phases, or even make them available for applications.…”
Section: Diagnosticsmentioning
confidence: 99%
“…This will enable a better understanding of the formation processes, possibly finding so far unknown novel phases, or even make them available for applications. While in-situ X-ray diffraction of laser-shock compressed samples has shown the formation of nano-diamonds, and even indicate that these survive the rapid (few nanoseconds) decompression to ambient densities 8 , their successful recovery remains a great challenge 55 . After shock-breakout the samples are ejected in the course of a free-surface release with velocities up to 20 km/s.…”
Section: Diagnosticsmentioning
confidence: 99%
“…Warm dense matter (WDM) is relevant for a plethora of applications such as inertial confinement fusion (ICF) [1,2], laboratory astrophysics [3,4], and material science at extreme conditions [5][6][7]. WDM is generated in experiments e.g.…”
Section: Introductionmentioning
confidence: 99%